GEGURITAN PURA TANAH LOT ANALISIS STRUKTUR DAN FUNGSI - Wiastika, IDa Bagus Putu (Humanis; Volume 12. No.1. Juli 2015)
This study examines the Pura Geguritan TanahLotkarya I Nyoman Suprapta . Geguritan inimenggunakan10 stanza types , namely : Maskumambang , Pucung , Ginanti , Mijil , Ginada , Durma , Semarandana , Pngkur , SINOM and Dangdang Sugar . Thisstudy structural menggunakanteori menurutTeeuwdan menurutEndraswara.Metode function theory and techniques used were divided into three stages , namely ( 1 ) phase of the provision of data by using the method and refer to the literature, supported by a technical reading , recording and translation , ( 2 ) the stage of data analysis using methods hermeneutic and descriptive , supported by the recording techniques , and ( 3 ) the stage presentation of the results of data analysis using informal methods , supported by deductive and inductive techniques . The results of this study is the first disclosure of the structure of the building Geguritan Tanah Lot temple good satuanforma maupunsatuan narrative . Then the second unfolding functions contained in Tanah Geguritan Lotyaitu discuss about how society should run a Hindu religious life . Satuanforma in this study include the code language and literature , variety of language and style . Unit meliputitema narrative , characterization , plot , setting , mythology in GPTL and hagiographical in GPTL . Function obtained in this study is the history of the establishment of Pura Tanah Lot , by Ida Dang Hyang Dwijendra as the main pastor . Functions obtained are: guiding functions in Bali Hindu religious life , trust the origin of the birth of Pura Tanah Lot or philosophy ( tattwa ) , an attitude of reverence and devotion or ethical ( moral ) and the customs of the Hindu tradition ( Event ) , the historic function of history Dharmayatra Ida Dang Hyang Dwijendra , and educational functions .
Keywords: geguritan , structure , function